Diseñar una propuesta de señalización horizontal y vertical para el centro de la ciudad de Loja bajo la normativa nevi-2012. - Carpio Reyes, Henrry Omar (2015)
This research work has as main objective the evaluation of the existing horizontal and vertical signaling in the center of Loja City, and propose a design proposal signaling both vertical and horizontal agree to the Standard Ecuadorian Vial - NEVI-2012 published by the Ministry of Transport and Public Works of Ecuador, with the aim of providing an alternative to increase road safety and improve traffic flow in the city of Loja. To meet the stated objective was performed an inventory of road signs, the state of road infrastructure and road hierarchy, by applying formats designed for the purpose. as complementary information were obtained traffic accidents reports occurred in the last three years .in the study zone From the obtained results was designed the proposal of vertical and horizontal signaling acording to the NAVY-2012 legislation, which will help improve road safety and traffic flow in the center of Loja city